Monte Carlo calculations in nuclear medicine : applications in diagnostic imaging - Ljungberg, Michael; Strand, Sven-Erik; King, Michael A. (New York: CRC Press, 2013)
"Preface Monte Carlo methods have become an important tool for exploring complicated systems and especially for investigation of imaging parameters in nuclear medicine. By using sampling methods based on probability distribution function in combination with methods that simulate the various particle interaction that can occur, a detailed radiation transport can be simulated from the patient into the imaging system. Monte Carlo simulation does not replace experimental measurements but offers a unique possibility to gain understanding in the underlying physics phenomena that form nuclear medicine images. It also provides a substantial help to researchers to develop methods for image improvement. When combining an accurate model of the imaging system and a realistic model of the patient's geometry and activity distribution, the simulated images can be highly clinically realistic and almost undistinguishable from a real patient measurement. The first edition of this book was published in 1998. It was one of the first books that combined a description of the Monte Carlo methods and principles with relevant Monte Carlo programs and applications in the field of diagnostic nuclear medicine. It is now 14 years since that publication and we therefore felt that it was important to have a second edition since new and very powerful Monte Carlo programs and methods have become available. This new edition provides the background to, and a summary of, the current Monte Carlo techniques that are in use today. The focus is still on the diagnostic imaging application but several programs that are described in the book also allow for charge-particle simulations applicable to dosimetryrelated applications"--
Includes bibliographical references and index.
Keywords: Monte Carlo method; Diagnostic imaging; MEDICAL / Radiology & Nuclear Medicine; SCIENCE / Physics; TECHNOLOGY & ENGINEERING / Biomedical